Sensibilização comportamental ao etanol e neuroadaptações envolvendo a proteína (DELTA)FOSB: efeitos do tratamento com N-Acetilcisteína em camundongos - Alves, Gabrielle Cunha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Pharmacological treatments currently used in ethanol addiction are inefficient, requiring new drugs for this purpose. The pro-drug N-Acetylcysteine (N-Ac) has shown efficacy in the treatment of addiction to cocaine and nicotine in preclinical research and clinical pilot studies. When administered, N-Ac is subsequently converted to cysteine, and cystine, which has an action on the central nervous system. However, there are few data about the possible application of N-Ac in the ethanol addiction. Behavioral sensitization is the gradual increase of the psychostimulant effects induced by repeated administration of drugs of abuse, including ethanol, and its development has been linked to important neuroadaptations in addiction. These neuroadaptations occur in neural circuits that mediate the reinforcing properties of these drugs and may involve several proteins. The ΔFosB protein accumulates in neurons after repeated activation and mediates long lasting changes in response to drugs of abuse. These changes are manifested mainly in the nucleus accumbens (Acb) and prefrontal cortex (PFC) neurons. The aim of the study was to evaluate the effects of N-Ac treatment in the development of ethanol behavioral sensitization and in alterations in the ΔFosB protein in mice. Swiss male mice were exposed to a standardized behavioral sensitization protocol to the experimental conditions of the laboratory and treated with N-Ac. At the end of behavioral sensitization procedure, animals were euthanized and their brains removed for ΔFosB quantification by Western blotting. Two experiments of behavioral sensitization were performed to the standardization of the protocol. The first, although effective in demonstrating the development of behavioral sensitization, was not effective in allowing the evaluation of the expression of the behavioral sensitization. The age of the animals and the conditions of luminosity and color of locomotion apparatus were changed and a new...

Os tratamentos farmacológicos empregados atualmente na dependência de etanol são pouco eficazes, sendo necessários novos fármacos para esse fim. O pró-fármaco N-Acetilcisteína (N-Ac) tem demonstrado eficácia no tratamento da dependência à cocaína e nicotina em pesquisas pré-clínicas e estudos clínicos piloto. Quando administrada, a N-Ac é convertida em cisteína e posteriormente em cistina, a qual tem ação no sistema nervoso central. Entretanto, existem poucos dados sobre a possível aplicação da N-Ac na dependência de etanol. A sensibilização comportamental consiste do aumento gradual do efeito psicoestimulante induzido pela administração repetida de drogas que induzem dependência, incluindo o etanol, e seu desenvolvimento tem sido relacionado à neuroadaptações importantes na dependência. Essas neuroadaptações ocorrem em circuitos neurais que medeiam o efeito reforçador dessas drogas e podem envolver várias proteínas. A proteína ΔFosB se acumula em neurônios após sua ativação repetida e medeia mudanças na resposta às drogas de abuso de forma bastante duradoura. Essas alterações se manifestam principalmente em neurônios do Núcleo Acumbens (Acb) e Córtex pré-frontal (CPF). Assim, o objetivo do presente estudo foi avaliar os efeitos do tratamento com N-Ac no desenvolvimento da sensibilização comportamental ao etanol e nas alterações da proteína ΔFosB em camundongos. Camundongos Suíços machos foram expostos a um protocolo de sensibilização comportamental padronizado para as condições experimentais do laboratório e tratados com N-Ac. Ao fim do procedimento de sensibilização comportamental, os animais foram eutanasiados e seus encéfalos retirados para quantificação de ΔFosB por western blotting. Foram realizados dois experimentos de padronização do protocolo de sensibilização comportamental. O primeiro, apesar de efetivo em demonstrar o desenvolvimento da sensibilização, não...
Keywords: Etanol; Córtex pré-frontal; Fármacos; Ethanol